Influence of an isotonic sports drink during exercise and recovery on subsequent endurance capacity and aldosterone response in the heat in well-trained endurance athletes - Fayiz AbuMoh`d, M. (SportMont, 2020)
This study was designed to investigate the influence of isotonic sports drink ingestion during exercise and recovery on subsequent endurance capacity, aldosterone, and other physiological responses in the heat. Twelve male well-trained endurance athletes (27.55±3.87 yrs) performed three experimental trials in which they ingested a sports drink (750 ml), water only or none. Each trial consisted of 3000 m run, 1 h recovery, and time to exhaustion test. The trials were randomized and separated by seven days. Drinks were administered in a crossover design, with the double-blind provision of sports drink and water. Blood samples were collected before and immediately after 3000-m, following recovery, and at exhaustion. A repeated-measures ANOVA test revealed no differences in the physiological responses before and after 3000 m run (p>0.05). After recovery, heart rate was significantly (p=0.050) lower in the sports drink trial than with water and control, with no differences were noted in the other physiological responses (p>0.05). At exhaustion, however, the data showed no differences in oral temperature and heart rate, but the differences were shown in aldosterone, blood glucose, and sodium (p<0.05). A post hoc Bonferroni test revealed that aldosterone was lower with the sports drink (602.33±18.68 pmol/L) than with water (688.08±29.03 pmol/L) and control (695.25±49.21 pmol/L). Endurance capacity was significantly greater with sports drink (56.53±2.53 min) than with water (51.16±1.80 min, p=0.001) and the control (50.09±3.00 min, p=0.001), without differences between the water and control trials (p=0.178). In conclusion, the ingestion of isotonic sports drink increases endurance capacity and maintains aldosterone more effectively than with or without water probably due to improved fluid retention.